Relation between contemplative exercises and an enriched psychology students' experience in a neuroscience course - Levit Binnun, Nava; Tarrasch, Ricardo (Frontiers in Psychology, 2014)
This article examines the relation of contemplative exercises with enhancement of students’ experience during neuroscience studies. Short contemplative exercises inspired by the Buddhist tradition of self-inquiry were introduced in an undergraduate neuroscience course for psychology students. At the start of the class, all students were asked to participate in short “personal brain investigations” relevant to the topic presented. These investigations were aimed at bringing stable awareness to a specific perceptual, emotional, attentional, or cognitive process and observing it in a non-judgmental, non-personal way. In addition, students could choose to participate, for bonus credit, in a longer exercise designed to expand upon the weekly class activity. In the exercise, students continued their “personal brain investigations” for ten minutes a day, four days a week. They wrote “lab reports” on their daily observations, obtained feedback from the teacher, and at the end of the year reviewed their reports and reflected upon their experiences during the semester. Out of 265 students, 102 students completed the bonus track and their final reflections were analyzed using qualitative methodology. In addition, 91 of the students answered a survey at the end of the course, 43 students participated in a quiz one year after course graduation, and the final grades of all students were collected and analyzed. Overall, students reported satisfaction from the exercises and felt they contributed to their learning experience. In the one-year follow-up, the bonus-track students were significantly more likely than their peers to remember class material. The qualitative analysis of bonus-track students' reports revealed that the bonus-track process elicited positive feelings, helped students connect with class material and provided them with personal insights. In addition, students acquired contemplative skills, such as increased awareness and attention, non-judgmental attitudes and b